Computational particle fluid dynamics simulation of biomass gasification in an entrained flow gasifier - Ramesh Timsina (Chemical Engineering Science: X, 2021)
Entrained flow gasification is an established technology for coal and petroleum coke particles. The technology is being investigated extensively for biomass gasification to meet the requirement of the green energy targets. A three-dimensional computational particle fluid dynamics (CPFD) model is developed to simulate an Entrained Flow (EF) gasification reactor. The model is validated against experimental gas composition and process temperature reported from an experiment published in the literature. The interdependence between reactor hydrodynamics, thermal and reaction chemistry is demonstrated and described for an EF reactor. Simulations show zones of high and low temperatures suggesting different reaction zones, such as a partial combustion zone near the fuel injector followed by a gasification zone. Particles in the central region show high carbon conversion compared to the particles in the other zones. Char- O₂ and char-H₂O are significant in the gasifier entrance region, whereas the char-CO₂ reaction is prevalent throughout the reactor elevation. The optimal gasification performance (higher mole fraction of CO and H₂) is in the range of equivalence ratio 0.3 to 0.44.